2020
DOI: 10.3389/fmicb.2020.569879
|View full text |Cite|
|
Sign up to set email alerts
|

Phosphorus Availability Promotes Bacterial DOC-Mineralization, but Not Cumulative CO2-Production

Abstract: The current trend of increasing input of terrestrially derived dissolved organic carbon (DOC) to boreal freshwater systems is causing increased levels of carbon dioxide (CO 2) supersaturation and degassing. Phosphorus (P) is often the most limiting nutrient for bacterial growth and would thus be expected to increase overall mineralization rates and CO 2 production. However, high carbon (C) to P ratios of terrestrially derived DOC could also cause elevated cell-specific respiration of the excess C in heterotrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 70 publications
(99 reference statements)
3
7
0
Order By: Relevance
“…Moreover, few dystrophic lakes have high levels of inorganic ions [64]. This is consistent with the findings of Allesson et al [18], who also suggested that at a community level, bacterial production increases relative to the bacterial respiration in nutrient-rich lakes. We thus suggest that in meso-and eutrophic lakes, the bacterial community uses a large proportion of the DNOM to grow and respire, although only a small part is used to provide energy for this growth.…”
Section: Enhanced Bacterial Respiration In Dystrophic Lakessupporting
confidence: 88%
See 2 more Smart Citations
“…Moreover, few dystrophic lakes have high levels of inorganic ions [64]. This is consistent with the findings of Allesson et al [18], who also suggested that at a community level, bacterial production increases relative to the bacterial respiration in nutrient-rich lakes. We thus suggest that in meso-and eutrophic lakes, the bacterial community uses a large proportion of the DNOM to grow and respire, although only a small part is used to provide energy for this growth.…”
Section: Enhanced Bacterial Respiration In Dystrophic Lakessupporting
confidence: 88%
“…Abbott et al [54] found that DP in their permafrost leachate samples was a good positive indicator of the percentage of BDOC. Similarly, Allesson et al [18] reported a higher turnover of BDOM in lakes in which P was in surplus. In our incubation experiment, all treatments received N and P to avoid the effects of nutrient limitation, in order to specifically test the role of DNOM quality on respiration.…”
Section: Priming Effect Boosting the Respiration Ratementioning
confidence: 84%
See 1 more Smart Citation
“…It is possible that the hyporheic microbial community in these nutrient polluted streams shifted its metabolism towards a higher assimilation of the provided DOM soil than respiration under P-enriched conditions. Similar effects have been found in Scandinavian lake waters where P additions increased bacterial growth and decreased cell-specific respiration at the same time (Allesson et al, 2020). However, more evidence is needed to confirm this mechanism here.…”
Section: No Microbial Stimulation By P Addition In Hyporheic Stream S...supporting
confidence: 84%
“…, phosphate) regulates carbon mineralization, and it is the most frequently reported limiting nutrient for bacterial production. 60–62 The sampled Nomi River water contains a higher phosphate concentration (2.73 mg L −1 ) than Tama River water (1.23 mg L −1 ). Considering that Nomi River water is more nutritious than Tama River water in terms of AOC and MAP, it was reasonable to expect more regrowth in Nomi River water under all conditions, consistent with our observation (Fig.…”
Section: Resultsmentioning
confidence: 99%